(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses technical regulations in the field of robotics, their practical application and importance. Technical regulations are important in the creation of robots and their safe operation. The article also provides information about the main norms and standards used in robotics. This article covers issues of current importance for specialists in the field.